Natural X-ray lines from the low scale supersymmetry breaking - Zhaofeng Kang; P. Ko; Tianjun Li; Yandong Liu (Physics Letters B, 2015)
In the supersymmetric models with low scale supersymmetry (SUSY) breaking where the gravitino mass is around keV, we show that the 3.5 keV X-ray lines can be explained naturally through several different mechanisms: (I) a keV scale dark gaugino plays the role of sterile neutrino in the presence of bilinear R-parity violation. Because the light dark gaugino obtains Majorana mass only via gravity mediation, it is a decaying warm dark matter (DM) candidate; (II) the compressed cold DM states, whose mass degeneracy is broken by gravity mediated SUSY breaking, emit such a line via the heavier one decay into the lighter one plus photon(s). A highly supersymmetric dark sector may readily provide such kind of system; (III) the light axino, whose mass again is around the gravitino mass, decays to neutrino plus gamma in the R-parity violating SUSY. Moreover, we comment on dark radiation from dark gaugino.